First description of Cryptosporidium hominis GP60 genotype IkA20G1 and Cryptosporidium parvum GP60 genotypes IIaA18G3R1 and IIaA15G2R1 in foals in Brazil - Inácio, Sandra Valéria [UNESP]; Zucatto, Anaiza Simão [UNESP]; de Aquino, Monally Conceição Costa [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Bresciani, Katia Denise Saraiva [UNESP]; Widmer, Giovanni; de Brito, Roberta Lomonte Lemos [UNESP]; Neto, Luiz da Silveira [UNESP]; Nakamura, Alex Akira [UNESP]; Meireles, Marcelo Vasconcelos [UNESP]; Carvalho, João Gabriel Balizardo [UNESP]; Gomes, Jancarlo Ferreira (Elsevier, 2017)
The present study focuses on Cryptosporidium infections of foals in Brazil. A total of 92 animals of different breeds from 11 farms in the vicinity of Araçatuba in the state of São Paulo, were examined. According to PCR targeting the 18S rRNA gene, Cryptosporidium sp. DNA was detected in 21.7% (20/92) of foals. Good quality 18S rRNA, actin, HSP70 and gp60 genes nPCR amplicons were obtained from five fecal samples. PCR amplification and sequencing of a fragment of the GP60 sporozoite surface glycoprotein gene revealed C. parvum genotypes IIaA18G3R1, IIaA15G2R1. Interestingly, we also detected in two foals a GP60 genotype related to the human parasite C. hominis.
Keywords: Equine; Molecular biology; Parasite